Assessment of the clinical cardiac drug‐drug interaction associated with the combination of hepatitis C virus nucleotide inhibitors and amiodarone in guinea pigs and rhesus monkeys. Issue 5 (23rd August 2016) - Regan, Christopher P.; Morissette, Pierre; Regan, Hillary K.; Travis, Jeffery J.; Gerenser, Pamela; Wen, Jianzhong; Fitzgerald, Kevin; Gruver, Shaun; DeGeorge, Joseph J.; Sannajust, Frederick J.
Abstract : In 2015, European and U.S. health agencies issued warning letters in response to 9 reported clinical cases of severe bradycardia/bradyarrhythmia in hepatitis C virus (HCV)‐infected patients treated with sofosbuvir (SOF) in combination with other direct acting antivirals (DAAs) and the antiarrhythmic drug, amiodarone (AMIO). We utilized preclinical in vivo models to better understand this cardiac effect, the potential pharmacological mechanism(s), and to identify a clinically translatable model to assess the drug‐drug interaction (DDI) cardiac risk of current and future HCV inhibitors. An anesthetized guinea pig model was used to elicit a SOF+AMIO‐dependent bradycardia. Detailed cardiac electrophysiological studies in this species revealed SOF+AMIO‐dependent selective nodal dysfunction, with initial, larger effects on the sinoatrial node. Further studies in conscious, rhesus monkeys revealed an emergent bradycardia and bradyarrhythmia in 3 of 4 monkeys administered SOF+AMIO, effects not observed with either agent alone. Morever, bradycardia and bradyarrhythmia were not observed in rhesus monkeys when intravenous infusion of MK‐3682 was completed after AMIO pretreatment. Conclusions : These are the first preclinical in vivo experiments reported to replicate the severe clinical SOF+AMIO cardiac DDI and provide potential in vivo mechanism of action. As such, these data provide a preclinical risk assessment paradigm, including a clinically relevant nonhuman primate model, with which to better understand cardiovascular DDI risk for this therapeutic class. Furthermore, these studies suggest that not all HCV DAAs and, in particular, not all HCV nonstructural protein 5B inhibitors may exhibit this cardiac DDI with amiodarone. Given the selective in vivo cardiac electrophysiological effect, these data enable targeted cellular/molecular mechanistic studies to more precisely identify cell types, receptors, and/or ion channels responsible for the clinical DDI. (Hepatology 2016;64:1430‐1441)